PERANCANGAN SISTEM INFORMASI PENJUALAN SOFTWARE BERBASIS WEB (STUDI KASUS PT. ELECTRONIC DATA INTERCHANGE INDONESIA) - kennedy, janero; fawaid, miftahul (Jurnal Teknologi dan Bisnis, 2019)
The process of selling software at PT. Electronic Data Interchange Indonesia is a very important thing besides the programmer division which is the company's kitchen, without sales the company is less effective. The purpose of writing is to design a system that can provide easier for companies in the process of selling software so that it will be more economical and communicative. The research method used in this research is using quantitative methods using primary and secondary data as samples. Primary data is taken from field observations in the workplace, namely by observing, interviewing customers and company employees. Secondary data is taken from available data by conducting a literature study. The software used in designing web-based software sales system applications is using the PHP programming language (Hypertext Preprocessor) and MySql as the database. The system development method used is the waterfall method with the modeling tools used are context diagrams, Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). The results achieved in the design of software sales systems by utilizing computer system technology to assist customers in buying products sold by PT. Electronic Data Interchange Indonesia practically. Conclusion The system is designed as simple as possible so that customers and companies can use it very easily.